Adult hippocampal neurogenesis is abundant in neurologically healthy subjects and drops sharply in patients with Alzheimer’s disease - Moreno-Jiménez, Elena P.; Flor-García, Miguel; Terreros-Roncal, Julia; Rábano, Alberto; Cafini, Fabio; Pallas-Bazarra, Noemí; Ávila, Jesús; Llorens-Martín, María (Nature medicine, 2019)
The hippocampus is one of the most affected areas in Alzheimer’s disease (AD) 1 . Moreover, this structure hosts one of the most unique phenomena of the adult mammalian brain, namely, the addition of new neurons throughout life 2 . This process, called adult hippocampal neurogenesis (AHN), confers an unparalleled degree of plasticity to the entire hippocampal circuitry 3 , 4 . Nonetheless, direct evidence of AHN in humans has remained elusive. Thus, determining whether new neurons are continuously incorporated into the human dentate gyrus (DG) during physiological and pathological aging is a crucial question with outstanding therapeutic potential. By combining human brain samples obtained under tightly controlled conditions and state-of-the-art tissue processing methods, we identified thousands of immature neurons in the DG of neurologically healthy human subjects up to the ninth decade of life. These neurons exhibited variable degrees of maturation along differentiation stages of AHN. In sharp contrast, the number and maturation of these neurons progressively declined as AD advanced. These results demonstrate the persistence of AHN during both physiological and pathological aging in humans and provide evidence for impaired neurogenesis as a potentially relevant mechanism underlying memory deficits in AD that might be amenable to novel therapeutic strategies. Newborn neurons are continuously incorporated into the healthy adult human hippocampus up to the ninth decade of life. However, robust adult hippocampal neurogenesis sharply declines during the progression of Alzheimer’s disease.